Investigating and increasing smokers’ use of effective cessation support - Murray, Rachael L. (2009)
Tobacco smoking is the leading avoidable cause of death and disability in the world. The UK is unique in that it offers a dedicated smoking cessation service providing behavioural support to all smokers, freely available through the National Health Service and with pharmacotherapy available at prescription cost. The service has been proven effective and cost-effective, yet only a small minority of smokers are currently using these services. The research in this thesis examines smokers’ use of support and how more smokers might be identified and encouraged to use it.